Environmental protection and shared management: a case study in the Metropolitan Region of Natal - Silveira, Raquel Maria da Costa; Figueiredo, Fábio Fonseca; Almeida, Jelisse Vieira Gomes (Pontifícia Universidade Católica de São Paulo, 2018)
In this paper, we aim to reflect on the relationship between the National Solid Waste Policy and the Metropolis Statute in order to understand the implications and challenges foreseen in these standards for the metropolitan regions in Brazil. Sharing solutions targeted at environmental preservation requires an agreement between different political and social actors, which sometimes creates obstacles to the existence of an effective policy. In this sense, we carried out a case study in the Metropolitan Region of Natal, in which we investigated, specifically, the shared management of solid waste in light of the federal law 12305/2010. The study showed lack of cooperation in the management of solid waste in the Metropolitan Region of Natal and revealed a scenario of noncompliance with the environmental law.